2017
DOI: 10.1016/j.biortech.2017.04.122
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of extremophilic exoelectrogens in microbial electrolysis cells using Red Sea brine pools as inocula

Abstract: Applying microbial electrochemical technologies for the treatment of highly saline or thermophilic solutions is challenging due to the lack of proper inocula to enrich for efficient exoelectrogens. Brine pools from three different locations (Valdivia, Atlantis II and Kebrit) in the Red Sea were investigated as potential inocula sources for enriching exoelectrogens in microbial electrolysis cells (MECs) under thermophilic (70°C) and hypersaline (25% salinity) conditions. Of these, only the Valdivia brine pool p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…It is therefore accepted that the successful application of BES to the treatment of highly saline and/or hot wastewater is based on the identification and characterization of exoelectrogenic bacteria that are both tenacious and resilient under these particularly extreme conditions. Halothermophilic microorganisms are thus suitable candidates for the treatment of the high saline wastewaters generated, for example, in the seafood processing (8 to 20 g/L), textile dyeing (2 to 10 g/L), petroleum (few g/L to 300 g/L), and tannery industries (40 to 80 g/L) [17,18]. Some halophilic and/or thermophilic bacterial species isolated from extreme natural or industrial environments have been reported to display electroactive properties [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore accepted that the successful application of BES to the treatment of highly saline and/or hot wastewater is based on the identification and characterization of exoelectrogenic bacteria that are both tenacious and resilient under these particularly extreme conditions. Halothermophilic microorganisms are thus suitable candidates for the treatment of the high saline wastewaters generated, for example, in the seafood processing (8 to 20 g/L), textile dyeing (2 to 10 g/L), petroleum (few g/L to 300 g/L), and tannery industries (40 to 80 g/L) [17,18]. Some halophilic and/or thermophilic bacterial species isolated from extreme natural or industrial environments have been reported to display electroactive properties [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Some halophilic and/or thermophilic bacterial species isolated from extreme natural or industrial environments have been reported to display electroactive properties [19,20]. In particular, sediments from salt marsh [7,8], saline microbial mats and salt lakes [21], saline ponds [22], the Red Sea [17], the Great Salt Lake [2], and Sambhar Lake [6] have been investigated to select electroactive bacterial biofilms. In the majority of these studies, a positive correlation between salinity and current generation has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…An example of an improved current generation at a high temperature (60°C) is a marine sediment MFC that generated 209-254 mA/m 2 compared with 10-22 mA/m 2 at 22°C [76]. Recently, an MFC with a higher operating temperature (70°C) has generated 6800 mA/m 2 [77]. Furthermore, the hyperthermophilic MFCs were operated at above 80°C [78].…”
Section: Psychrophiles and Thermophilesmentioning
confidence: 99%
“…MEC gets noticeable attention as a sustainable wastewater treatment system with energy recovery [33], and many research teams built pilot scale MEC facilities to validate that MEC can be utilized in real industry [34][35][36][37][38][39]. In recent studies, various modified MEC structures are suggested for different applications, such as microbial electrodialysis cell (MEDC) [40], microbial reverse-electrodialysis electrolysis cell (MREC) [41,42], microbial electrolysis struvite-precipitation cell (MESC) [43][44][45], microbial electrolysis desalination and chemical-production cell (MEDCC) [46][47][48][49], and microbial saline-wastewater electrolysis cell (MSC) [50][51][52].…”
Section: Introductionmentioning
confidence: 99%